Dietary Compound Isoliquiritigenin Inhibits Breast Cancer Neoangiogenesis via VEGF/VEGFR-2 Signaling Pathway - Wang, Zhiyu; Wang, Neng; Han, Shouwei; Wang, Dongmei; Mo, Suilin; Yu, Linzhong; Huang, Hui; Tsui, Kamchuen; Shen, Jiangang; Chen, Jianping (PLOS ONE, 2013)
Angiogenesis is crucial for cancer initiation, development and metastasis. Identifying natural botanicals targeting angiogenesis has been paid much attention for drug discovery in recent years, with the advantage of increased safety. Isoliquiritigenin (ISL) is a dietary chalcone-type flavonoid with various anti-cancer activities. However, little is known about the anti-angiogenic activity of isoliquiritigenin and its underlying mechanisms. Herein, we found that ISL significantly inhibited the VEGF-induced proliferation of human umbilical vein endothelial cells (HUVECs) at non-toxic concentration. A series of angiogenesis processes including tube formation, invasion and migration abilities of HUVECs were also interrupted by ISL in vitro. Furthermore, ISL suppressed sprout formation from VEGF-treated aortic rings in an ex-vivo model. Molecular mechanisms study demonstrated that ISL could significantly inhibit VEGF expression in breast cancer cells via promoting HIF-1α (Hypoxia inducible factor-1α) proteasome degradation and directly interacted with VEGFR-2 to block its kinase activity. In vivo studies further showed that ISL administration could inhibit breast cancer growth and neoangiogenesis accompanying with suppressed VEGF/VEGFR-2 signaling, elevated apoptosis ratio and little toxicity effects. Molecular docking simulation indicated that ISL could stably form hydrogen bonds and aromatic interactions within the ATP-binding region of VEGFR-2. Taken together, our study shed light on the potential application of ISL as a novel natural inhibitor for cancer angiogenesis via the VEGF/VEGFR-2 pathway. Future studies of ISL for chemoprevention or chemosensitization against breast cancer are thus warranted.